Exploring Students and Teachers’ Anxiety in Learning English During Emergency Remote Teaching in Vocational High School in Bangli - Vera Yanti Made; Made Hery Santosa; Gede Mahendrayana (EDUVELOP, 2022)
English is one of the languages that are used in universal and the important thing to all people learnt nowadays. As an EFL learner learning English is not easy especially in a pandemic situation. The students cannot study face to face and should change into emergency remote teaching. In doing the online learning the students find difficulties such as they have a limited time in learning. The aimed of this study is to explore the anxiety level of students and teachers in learning English during emergency remote teaching. Therefore, study through online learning is a new thing for them. The method of this study was quantitative to collect the data. The data was done by doing the survey and giving a questionnaire that was develop based on FLACS. The participants of this study are 183 students of 10th grade and 4 teachers of English language in vocational high school in Bangli. The result of this study showed that the students’ anxiety was mildly anxious or it can be indicated as a moderate level of anxiety and for the teachers was relaxed or it can be indicated as a low level of anxiety. It can be concluded that the students in learning English not enjoyed but not nervous it is in the middle. For the teacher, they really relaxed in teaching English during the emergency remote teaching.